Understanding the role of brand respect and brand love as a strategy to accelerate lovemarks (survey on the Garuda Airline special for Hajj) - Titisania Rimadewi, Anantasha (Central Research Institute for Agriculture (CeRIA), 2024)
Today, product innovation and technological services of international airlines, especially Hajj airlines, are growing at a rapid pace. Each airline is competing to make various innovations and issue promotions, so that the market is flooded with various airline products specifically for the pilgrimage. There is still little research on Brand Respect and Brand Love and their influence on Lovemarks, especially on special masks for Hajj. The foregoing is the basis for the urgency of this research. The purpose of this study is to contribute to supporting previous research with different samples and eliminated variables. This study also aims to determine whether Lovemarks, which are explained by intimacy, sensualilty and mystery have a correlation with brand love and brand respect. Through quantitative research, it can be concluded that brand love and brand respect have a positive effect on Lovemarks, brand love has the greatest influence on Lovemarks.